2020
DOI: 10.1186/s12870-020-02671-2
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based comparative proteomic analysis of differences in the protein profiles of stems and leaves from two alfalfa genotypes

Abstract: Background To explore the molecular regulatory mechanisms of early stem and leaf development, proteomic analysis was performed on leaves and stems of F genotype alfalfa, with thin stems and small leaves, and M genotype alfalfa, with thick stems and large leaves. Results Based on fold-change thresholds of > 1.20 or < 0.83 (p < 0.05), a large number of proteins were identified as being differentially enriched between the M and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Generally, pastures progress in their development cycle, increasing the proportion of stems and reducing leaf production [59,60]. Additionally, as observed by Sun et al [61], as plant phenological stages progress and their leaves age, there is a continuous decrease in total nitrogen and crude protein levels. This trend, accompanied by the increased lignification of leaves and stems, justifies the notable reduction in the N and protein content in plants as grazing cycles advance, as well as the neutralization of fertilizer effects on forage composition.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, pastures progress in their development cycle, increasing the proportion of stems and reducing leaf production [59,60]. Additionally, as observed by Sun et al [61], as plant phenological stages progress and their leaves age, there is a continuous decrease in total nitrogen and crude protein levels. This trend, accompanied by the increased lignification of leaves and stems, justifies the notable reduction in the N and protein content in plants as grazing cycles advance, as well as the neutralization of fertilizer effects on forage composition.…”
Section: Discussionmentioning
confidence: 95%
“…The former detected 28 miRNAs differentially expressed at both 2 days and 10 days after low K stress for two barley genotypes [ 91 ], while the latter found miR9772, miR1120b-3p, miR531, and miR319 displaying differential expression at all time points during the low K treatments, and suggested that these miRNAs were most possibly involved in mediating plant adaptation to K deficiency [ 118 ]. Interestingly, high-throughput sequencing was also employed for identifying differentially expressed miRNAs between two transgenic tomato plants, separately overexpressing SlmiR168a and SlAGO1 , to explore downstream miRNAs (miR171, miR384, miR530, miR858, and miR8007) involved in the SlmiR168 -mediated SlAGO1A regulation upon K stress [ 119 ].…”
Section: Large-scale Identification Of Mirnas Responsive To Differential Nutrient Availabilitymentioning
confidence: 99%
“…Every three individual samples were pooled for one replicate, and three biological replicates were analyzed. Total protein was isolated and purified according to a previously published study [90]. Additionally, protein concentration was measured using a Bradford assay kit (Bio-Rad Laboratories Inc., Hercules, CA, USA), and bovine serum albumin (BSA) was used as a reference protein for this experiment to generate a standard curve.…”
Section: Itraq-based Comparative Proteomic Analysismentioning
confidence: 99%